Philosophical foundations of fiduciary law - Gold, Andrew S.; Miller, Paul B. (Oxford : Oxford University Press, 2014)
Fiduciary law is one of the most important areas of private law, governing a wide range of relationships that affect people in their daily lives. These new and innovative essays explore the foundations of fiduciary relationships and the duties fiduciaries owe to their beneficiaries.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Trusts and trustees -- Philosophy; Law; Laws of specific jurisdictions & specific areas of law